Identifikasi dan Proyeksi Timbulan Sampah Mengandung B3 Rumah Tangga di DKI Jakarta - Wahyu Dewi Yantini; I Made Wahyu Widyarsana (Jurnal Serambi Engineering, 2025)
The growing population and increased community activities in DKI Jakarta have resulted in higher waste generation, averaging 0.7 kg per person per day, or 7,800 tonnes, which is primarily disposed of at the Bantargebang TPST. Although dominated by organic and inorganic waste, household hazardous waste (HHW) is also found at the community level. This is attributed to the use of chemical products in household activities, such as cleaning and personal care products, paints, pesticides and electronics. A study of 150 households of different income levels found an average generation of HHW of 0.0097 kg per person per day, with specific averages of 0.0098 kg, 0.009 kg and 0.01 kg for low, middle and high income levels respectively. HHW consists mainly of packaging waste from personal care and beauty products (28.62%), cleaning and household products (26.34%) and leftover medicine/medical waste (23.17%). HHW with infectious (39.32%) and toxic (35.63%) properties are more common than other properties. Waste generation projections, modelled using a simple dynamic system simulation, estimate that waste generation will reach 106,688.02 tonnes per year over the next 20 years.